A Continuous Casting Device with Electromagnetic Stirring for Production of SSM Feedstock Using Al-Si Alloys - Wendel Leme Beil; Gabriela Lujan Brollo; Eugênio José Zoqui (Materials Research, 2021)
Abstract This work describes the design, construction and testing of a continuous casting device coupled to an electromagnetic stirring system for the production of thixoforming feedstock using Al-Si alloys. The following processing and construction parameters were tested: pouring temperature (660-800 °C), mould cavity roughness (Ra = 0.17-1.06 µm), casting speed (2-4 mm/s), use of a combined (primary and secondary) cooling system and the intensity and radial penetration of electromagnetic stirring (0, 1500 and 3000 W stator power). The macro-appearance of the ingots and the longitudinal and radial microstructural parameters were then evaluated. The results indicate that the surface finish of the mould cavity was an important construction parameter as it had a strong influence on heat transfer and, consequently, feed speed; use of a secondary cooling system for the mould allowed greater grain refinement and microstructural homogeneity to be achieved for all the conditions tested; optimal electromagnetic stirring power was 1500 W (EMFmax = 22 Gauss); this resulted in a grain size-to-dendritic arm spacing ratio of close to 1, which is suitable for subsequent SSM processing.